'Sorry we do not deliver to your area': geographical inequalities in online groceries provision. Issue 1 (1st January 2022) - Newing, Andy; Hood, Nick; Videira, Francisco; Lewis, Jack
ABSTRACT: The British grocery retail sector is experiencing rapid growth in online ordering for home delivery, resulting in considerable supply side investment in delivery and fulfilment infrastructure. For retailers with a physical store network, investments typically utilise larger format stores as delivery and fulfilment hubs. Proximity to the store network and delivery infrastructure capacity thus drive the availability and choice of online groceries provider at the neighbourhood level. We aim to assess the geographical extent of online groceries coverage at a small-area level in Great Britain (GB). We carry out a nationwide assessment of the provision of online groceries, revealing generally excellent coverage within urban and suburban areas, including those neighbourhoods that may have once been considered urban food deserts. However, rural–urban inequalities are evident, with the most remote and rural catchments experiencing comparatively poor online groceries provision. We argue that these inequalities give rise to a new form of food desert: remote and rural neighbourhoods with the compounded effects of poor access to physical retail provision (akin to 'traditional' food deserts) and the additional disadvantage of poor coverage by online groceries providers. Many of these neighbourhoods are already the most remote from physical store provision and may also be faced with withdrawal of physical (retail) services. We make a number of recommendations that could support the provision of online groceries services in these areas and reflect on the tremendous potential for ongoing research into widening inequalities in access to grocery retailing driven by the geography of online groceries.